Revitalizing the Value of Tolerance in Islamic Religious Education (PAI) Learning to Face the Challenges of Multiculturalism - Muzaki, Muzaki; Firdaus, Saihan; Mustajab, Dadang (FKIP - Universitas Riau, 2025)
The increasingly pluralistic global society has greatly influenced the dynamics of Islamic Religious Education (IRE), which plays a vital role in shaping students’ moral and spiritual character. In Indonesia’s multicultural context, IRE faces challenges in cultivating tolerance amid social polarization, religious exclusivism, and moral disintegration in the digital era. This study aims to analyze the strategies and implementation of tolerance value revitalization in IRE learning as a response to multicultural challenges in modern education. Using a qualitative descriptive approach with a library research method, this research examines classical Islamic literature, contemporary studies, and national education policies. The analysis highlights Islamic principles such as tasamuh (tolerance), ta’awun (cooperation), ukhuwah insaniyah (human fraternity), and ‘adl (justice) as foundational values for social harmony and peace. The findings reveal that IRE can effectively foster multicultural awareness when learning processes are reflective, dialogical, and contextual. Revitalization of tolerance values is realized through curriculum reform promoting religious moderation, teacher exemplarity as moral role models, and the development of inclusive educational environments. The study concludes that revitalizing tolerance in IRE is essential for building students’ humanistic character and strengthening national unity in a diverse society.